Design of a Superconducting Antenna Integrated with a Diplexer for Radio-Astronomy Applications - Donelli, Massimo; Febvre, Pascal (Journal of Telecommunications and Information Technology, 2014)
This paper presents the design of a compact frontend diplexer for radio-astronomy applications based on a self complementary Bow-tie antenna, a 3 dB T-junction splitter and two pass-band fractal lters. The whole diplexer structure has been optimized by using an evolutionary algorithm. In particular the problem of the diplexer design is recast into an optimization one by dening a suitable cost function which is then minimized by mean of an evolutionary algorithm namely the Particle Swarm Optimization (PSO). An X band diplexer prototype was fabricated and assessed demonstrating a good agreement between numerical and experimental results.
Keywords: diplexer; microwave antenna; optimization techniques; particle swarm algorithm; radio-astronomy